A Lagrangian model-based physical connectivity atlas of the Red Sea coral reefs - Wang, Yixin; Raitsos, Dionysios E.; Krokos, George; Zhan, Peng; Hoteit, Ibrahim (Frontiers in Marine Science, 2022)
Connectivity, the exchange of individuals and genes among geographically separated marine populations, plays a key role in coral reef biodiversity and resilience. The Red Sea is a semi-enclosed basin with dynamic circulation and abundant coral reefs, making it a natural laboratory for coral reef connectivity research. Previous studies broadly investigated Red Sea connectivity, but were spatially restricted to regional or sparsely-distributed reef sites. Here, using hydrodynamic and particle tracking models, a high-resolution circulation-driven physical connectivity atlas covering every Red Sea coral reef, including seasonality, was simulated and further validated against available in-situ genetic datasets. The simulation was conducted without incorporating larval traits to isolate and quantify the connectivity contributed by circulation. Our validation experiment suggests the importance of circulation in shaping the genetic structure of Red Sea reef species, supporting the Isolation By Circulation (IBC) theory in the Red Sea seascape genetics. The simulated atlas reveals that reefs in the northern Red Sea are better sources and destinations than those in the southern basin, regardless of season. The east-west connections between the southern reefs are identified to be weak. Complex circulation dynamics drive a regional-specific seasonality, e.g., the Farasan Islands reefs are better sources during summer while the nearby Bab-Al-Mandeb strait reefs are better sources during winter. The west-coast reefs are generally winter-intensified sources whereas the east-coast reefs are generally summer-intensified sources. The revealed seasonality of physical connectivity is important for larval dispersal processes as reef species may spawn in different seasons. This physical connectivity atlas provides a reference for designing marine conservation strategies from a circulation perspective and easy-to-access physical connectivity datasets for the future Red Sea seascape genetic studies.